A socio-technical approach to design for community resilience: A framework for analysis and design goal forming. (September 2015) - Baek, Joon Sang; Meroni, Anna; Manzini, Ezio
Abstract : This paper presents a finding on the application of socio-technical systems design to analyse community resilience and develop design goals to enhance it. It describes a framework for diagnosing the resilience of people's social networks and developing strategies based on network theory. It goes on to outline the methodology and findings of a case study exploring the application of this framework in analysing producers' collaborative networks around a farmers' market in Milan. Based on the analysis, the paper explores the perceived feasibility of this framework as a preliminary stage to develop collaborative services. It concludes by commenting on the wider implications of the framework to design for sustainable services. Highlights: We propose a socio-technical framework to analyse community resilience. The framework aims at enhancing the resilience of a social system through the design of a technical system. We demonstrate the framework in a case study to develop services around a farmer's market in Milan. We analyse the producers' collaborative network, diagnose its resilience, and develop strategies to improve it. The framework is applicable to the design of socio-technical systems whose resilience is at stake.